Cost Overruns and Demand Shortfalls in Urban Rail and Other Infrastructure - Flyvbjerg, B (Taylor and Francis, 2007)
Risk, including economic risk, is increasingly a concern for public policy and management. The possibility of dealing effectively with risk is hampered, however, by lack of a sound empirical basis for risk assessment and management. This article demonstrates the general point for cost and demand risks in urban rail projects. The article presents empirical evidence that allow valid economic risk assessment and management of urban rail projects, including benchmarking of individual or groups of projects. Benchmarking of the Copenhagen Metro is presented as a case in point. The approach developed is proposed as a model for other types of policies and projects in order to improve economic and financial risk assessment and management in policy and planning.